PV integrated single-phase dynamic voltage restorer for sag voltage, voltage fluctuations and harmonics compensation - Toufik Toumi; Ahmed Allali; Othmane Abdelkhalek; Abdallah Ben Abdelkader; Abdelmalek Meftouhi; Mohammed Amine Soumeur (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This document proposes a photovoltaic (PV) based single-phase dynamic voltage restoration (DVR) device, it eliminates both sag and swell voltage and compensates for power. The proposed system requires a power source to compensate for the sag/swell voltage. This system has found a simple topology for the DVR that uses PV with two DC-DC boosts converters as the DC power source for the dynamic voltage conservator. The DC/DC boost converter powered by the PV generator is used to increase the voltage to meet the DC bus voltage requirements of the single-branch voltage source inverter (VSI). This system uses renewable energy; saves energy accordingly and supplies power to critical/sensitive loads. The control method used in this work is a Sliding Mode Control (SMC) method and relies on a phase locked loop (PLL) used to control the active filter. The effectiveness of the suggested method is confirmed by the MATLAB/Simulink® simulation results and some prototype experiments. These results show the capacity of the proposed DC link control.